W pogoni za zrozumieniem: polskie tłumaczenia ekranizacji serii "Bridget Jones" = The edge of meaning: Polish translations of the "Bridget Jones" film series - Plewa, Elżbieta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This paper analyses Polish translations of two romantic comedy films "Bridget Jones' Diary" and "Bridget Jones' Baby". The main goal of a translated text is to convey the meaning of an original. However, it is impossible for any two persons to deliver identical translations. It is always an individual, unique text of the particular author - a film translator and it reflects his or her idiolect.
Keywords: pamiętnik; tłumaczenie audiowizualne; tłumaczenie filmowe; tłumaczenie lektorskie; tłumacz filmowy; diary; audiovisual translation; film translation; voice-over; film translator